The Potential of Rosuvastatin in Stabilizing Lipid Profile and Improving Clinical Outcomes in Covid-19 Patients with Coronary Heart Disease - William Suciangto; Haerani Rasyid; Nada Indira Ramadhani Nasrum; Muhammad Zaki Rahmani (Faculty of Medicine, Hasanuddin University., 2021)
Introduction : The novel coronavirus disease (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), remains a global challenge since December 2019 cause by its severe symptoms and high mortality rate. Some comorbidities are associated with clinical outcomes in COVID-19 patients, one of them is cardiovascular disease, including coronary heart disease (CHD). Statins are popularly used as the lipid controller in CHD patients. Not only controlling the lipid profile, statins also can reduce the inflammation process in COVID-19 patients. This review aims to determine the activity of statins and its potential to improve the clinical manifestation of COVID-19 patients with CHD. Methods : The method used in this paper is to examine and review the literature journal that has been published last 10 years. Results : Recent studies have shown that statins capable to control the lipid, also lowering the LDL cholesterol and increasing the HDL cholesterol. And other trials have shown that statin also have ability to reduce the inflammation and inhibit further cell damage by binding mpro, a protease produced by SARS-COV2. Conclusions: Based on those studies, we conclude that statins have the potential effect as adjuvant therapy for clinical improvement in COVID-19 patients with CHD.